VORTEX HYDRAULIC HEAT GENERATOR – ALTERNATIVE POWER SOURCE - Biryik, V.; Serebryakov, R. (Energy and Automation, 2016)
The article describes the basic principles of hydraulic vortex heat generators (VGT), a variant of the theoretical foundations of the work of the VGT and the method of evaluating the performance of VGT.